Measuring Performance during Challenging Times: Rethinking the Performance Evaluation System - Andreea Daniela TUDOR (Communications of International Proceedings, 2021)
A funny thing that you discover when you start measuring work is that it varies within an organization more than between one organization and another. The inconsistency in measuring performance that was present before COVID-19 has amplified after the virus appeared. This mainly happens because of the discrepancies between the leadership styles and the beliefs about what is performance and how it needs to be measured, adding the confusion regarding the choice of adjusting of not adjusting the expectations. Management & leadership representatives agree that nowadays the fundamental particularity of a performance management should be focusing on people because they can make a difference, raising the level of performance over time. During COVID-19 pandemic crisis, managers all over the world agreed that the best way to approach performance management is with more flexibility, empathy, indulgence and compassion. Also, finding ways to show appreciation and recognition for the employees that stay committed during those difficult times is a very important factor that plays a role in the level of performance in organizations. Management representatives believe this helps amplify the employee engagement, morale and productivity during the crisis.
Keywords: Performance Management; Leadership; Results; COVID-19; Pandemic Crisis; Benchmarking.